2014
DOI: 10.1007/s12639-014-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ectoparasites in free-range backyard chickens, domestic pigeons (Columba livia domestica) and turkeys of Kermanshah province, west of Iran

Abstract: This study was carried out on free-range backyard chickens, domestic pigeons (Columba livia domestica) and turkeys from May 2012 to April 2013 to determine the prevalence and identify the species of ectoparasites in Kermanshah province, west of Iran. Of the total of 600 free-range backyard chickens (185 # and 415 $), 700 domestic pigeons (278 # and 422 $) and 150 turkeys (53 # and 97 $), 389 (64.83 %), 608 (86.85 %) and 54 (36 %) were infected with one or more parasites respectively. Eleven ectoparasites speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
18
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 22 publications
12
18
6
Order By: Relevance
“…Our results regarding the age of animal were in disagreement with the findings of Mulugeta et al (2013), Firaol et al (2014) and Rezaei et al (2016) who reported that young chickens were more infested than adult animals.…”
Section: Journal Of Animal Health and Productioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results regarding the age of animal were in disagreement with the findings of Mulugeta et al (2013), Firaol et al (2014) and Rezaei et al (2016) who reported that young chickens were more infested than adult animals.…”
Section: Journal Of Animal Health and Productioncontrasting
confidence: 99%
“…Among the identified flea species, Echidnophaga gallinacea was detected in 2 ± 1.22% of examined birds. The prevalence of this ectoparasite in our study was not similar to those reported from west of Iran with 6% (Rezaei et al, 2016), 18% in California (Murillo and Mullens, 2016), 29.6% in Abuja (Nigeria) (Odenu et al,. 2016), 27.3% in Gombe (Nigeria) (Lawal et al, 2016) and from different regions in Ethiopia with 26.6% (Mata et al, 2018) to 51.3% (Belihu et al, 2009).…”
Section: Journal Of Animal Health and Productioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Mites (78.8%), lice (63.1%) and worm (44.1%) were commonly observed compared to fleas and ticks among the poultry population (see table 6). Anaemia, prolong maturity, poor feed utilization, drop in production, and irritation, were apparent clinical conditions described by farmers which are in agreement with (23,24) reports. Chart 1 illustrates the different approaches farmers used when there is an outbreak of parasitic infestation.…”
Section: Table6 Common Diseases and Parasites Listed By Farmerssupporting
confidence: 88%
“…An examination of poultry houses in private holdings in Southern California found poultry mites D. gallinae -55%, Menacanthus stramineus chewing lice -5%, Goniocotes gallinae -3%, Lipeurus caponis -20%, Menopon gallinae -15%, Cuclotogaster heterographs -5%; Echidnophaga gallinacea fleas -20%, parasitic mites Ornithonyssus sylviarum -15% and Knemidocoptes mutans -10% (Murillo & Mullens, 2016). According Rezaei et al (2016), during the examination of poultry houses in Colombia, D. gallinae mites were detected in 8.5% of households. Also, ectoparasites such as Menacanthus stramineus, M. gallinae, Cuclotogaster heterographus, Goniocotes gallinae, Ornithonyssus bursa, K. mutans were found.…”
Section: Introductionmentioning
confidence: 99%